2019
DOI: 10.1021/acs.langmuir.9b00606
|View full text |Cite
|
Sign up to set email alerts
|

Conduction and Excess Charge in Silicate Glass/Air Interfaces

Abstract: The glass/air interface shows electrical properties that are unexpected for a widely used electrical insulator. The mobility of interfacial charge carriers under 80% relative humidity (RH) is 4.81 × 10 −5 m 2 s −1 V −1 , 3 orders of magnitude higher than the electrophoretic mobility of simple ions in water and less than 2 orders of magnitude lower than the electron mobility in copper metal. This allows the glass/air interface to reach the same potential as a biased contacting metal quickly. The interfacial sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It is known that silicon oxide or glass show significant surface conduction at a humidity above E40%. [57][58][59] This surface conduction may lead to discharging via the back electrode, or at least to a diffusion of charge away from the area where the charges were deposited.…”
Section: Series Of Dropsmentioning
confidence: 99%
“…It is known that silicon oxide or glass show significant surface conduction at a humidity above E40%. [57][58][59] This surface conduction may lead to discharging via the back electrode, or at least to a diffusion of charge away from the area where the charges were deposited.…”
Section: Series Of Dropsmentioning
confidence: 99%
“…In the time between two drops, ∆t, the surface charge will gradually dissipate, e.g. through non-zero substrate or surface conductivity [32][33][34][35] or by neutralization through ionic species in the air [36]. As a first-order approximation, we assume that these processes introduce an effective surface resistance, dR on each surface element dA, leading to an exponentially decaying surface charge with characteristic decay time τ = dRc s dA.…”
mentioning
confidence: 99%
“…The characteristic time of charge dissipation was less than 0.1 seconds in this case. 173 Various functional relationships between humidity and surface conduction have been reported in previous studies. Some studies reported that the surface conductivity of insulating materials increased approximately exponentially with increasing humidity.…”
Section: Surface Conductionmentioning
confidence: 89%
“…161,165 Other studies suggested that a threshold humidity was involved for other materials. 171,173,174 Below the threshold, the surface conductivity did not increase signicantly as humidity increased; above the threshold, the surface conductivity increased drastically as humidity increased.…”
Section: Surface Conductionmentioning
confidence: 99%
See 1 more Smart Citation